Pekanbaru Entertainment Center Dengan Pendekatan Arsitektur Modern Berdasar Konsep "Less Is More" - Rendy Musamel; Pedia Aldy; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Current development in the world of work is increasing causing humans to spend time to working. It is a lot happening in the big cities as well as in the cities is growing. Human activities that are constantly working unconsciously cause boredom and increase the levels of stress on themselves. Based on the balance between work and entertainment, we need a place to meet the needs of entertainment for the community. Therefore, Entertainment Center is one place solutions that can accommodate the needs of entertainment for the community. Entertainment Center is a building that is both attractive as well as recreational and commercial, a building that can accommodate a variety of entertainment facilities which have different properties and types. In designing Entertainment Center made the approach on modern architecture based on “less is more” and the concept of unification of the character and function of the building. This is related to the unification of various types of entertainment that are for individuals, groups or families that are adjusted to the nature of the area (public, semi-public, private) with the application of modern themes in interior and exterior, the building materials, circulation and spatial relations in building. Entertainment Center so that it can be a place to meet the needs of entertainment for the community to relieve tired and bored of the daily activities, and can accommodate people pleasure in enjoying life.Keywords: Entertainment Center, Modern Architecture, Less Is More, Character and Function of Building